2001
DOI: 10.2118/69197-pa
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Monitoring of Surfactant Imbibition With Computerized Tomography

Abstract: Summary Oil production from fractured reservoirs can occur by spontaneous water imbibition and oil expulsion from the matrix into the fracture network. Injection of dilute surfactant can recover additional oil by lowering oil/water interfacial tension (IFT) or altering rock wettability, thereby enhancing countercurrent movement and accelerating gravity segregation. Modeling of such recovery mechanisms requires knowledge of temporal and spatial fluid distribution within porous media. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 13 publications
1
46
0
Order By: Relevance
“…These projects are the Cottonwood Creek in the Bighom Basin of Wyoming (Xie et al 2005;Weiss et al 2006), the Yates field in Texas (Yang and Wadleigh 2000; Chen et al 2001), and the Baturaja formation in the Semoga field in Indonesia (Rilian et al, 2010).…”
Section: [82]summary Of Surfactant Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These projects are the Cottonwood Creek in the Bighom Basin of Wyoming (Xie et al 2005;Weiss et al 2006), the Yates field in Texas (Yang and Wadleigh 2000; Chen et al 2001), and the Baturaja formation in the Semoga field in Indonesia (Rilian et al, 2010).…”
Section: [82]summary Of Surfactant Projectsmentioning
confidence: 99%
“…Hirasaki and Zhang (2004) used ethoxylated and propoxylated sulfates. Nonionic surfactants were used by Chen et al (2001) and Xie et al (2005). For more details, see Sheng (2013b).…”
Section: [84]chemicals Usedmentioning
confidence: 99%
“…Not only the recovery mechanism of surfactant flooding in porous media is not very well modeled and described so far, but also adding other affecting parameters such as porous medium heterogeneities, interaction between surfactants and reservoir fluids, and surfactant adsorption leads to growth of its complexity [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Standnes and Austad (2003) conducted imbibition and contact angle measurements using chalk and reservoir dolomite cores and showed the surfactant-induced wettability alterations from oil-wet to water-wet. Chen et al (2001) performed dilute surfactant imbibition tests on initially oil-wet dolomite cores of Yates field and measured USBM wettability indices to demonstrate the ability of surfactants to shift the wetting characteristics of Yates rock towards less oil-wet. Ayirala and Rao (2004) conducted corefloods with dilute surfactants using Berea sandstone cores and Yates reservoir fluids and found that the surfactants can also develop mixed-wettability in an initially water-wet system.…”
Section: Introductionmentioning
confidence: 99%